#### Answer

$-\frac{5}{2}$

#### Work Step by Step

$\frac{5x-20}{8-2x}$
$=\frac{-5x+20}{2x-8}$
$=\frac{-5(x-4)}{2(x-4)}$
$=-\frac{5}{2}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$-\frac{5}{2}$

$\frac{5x-20}{8-2x}$
$=\frac{-5x+20}{2x-8}$
$=\frac{-5(x-4)}{2(x-4)}$
$=-\frac{5}{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.